Effect of intermittent fasting after ST-elevation myocardial infarction on left ventricular function: study protocol of a pilot randomised controlled trial (INTERFAST-MI). Issue 4 (7th April 2022) - Dutzmann, Jochen; Knöpp, Kai; Kefalianakis, Zoe; Daniel, Jan-Marcus; Gufler, Hubert; Wohlgemuth, Walter; Kahles, Florian; Sedding, Daniel G
Abstract : Introduction: Preclinical studies consistently show robust disease-modifying effects of intermittent fasting in animal models of cardiovascular disease. However, the impact of intermittent fasting on cardiovascular endpoints after myocardial infarction has not been investigated in a clinical trial so far. Methods and analysis: The INTERmittent FASTing after Myocardial Infarction (INTERFAST-MI) trial is a monocentric prospective randomised controlled non-confirmatory pilot study including 48 patients with ST-segment elevation myocardial infarction. They will be randomised in a 1:1 ratio to either intermittent fasting (daily time-restricted eating; consuming food for not more than 8 hours/day, fasting for at least 16 hours/day) or to a control group without a particular diet. The follow-up time is 6 months. The prespecified primary outcome is change in left ventricular systolic function at 4 weeks from baseline to estimate effect size required to establishing sample size and power calculation for a future full-scale trial. Secondary outcomes include protocol adherence, recruitment, major adverse cardiac events, revascularisation, changes in left ventricular systolic function at 3 and 6 months, patient weight, blood pressure, and serum markers of inflammation and cardiovascular disease. Enrolment began on 1 November 2020 and is expected to conclude in December 2021. Ethics and dissemination: The trial has received ethics approval from the Medical Ethics Committee of the Martin-Luther-University Halle-Wittenberg. Results of the study will be submitted for publication in a peer-reviewed journal and presented at scientific conferences. Trial registration number: DRKS00021784.